The death of the Messiah and the birth of the new covenant : a (not so) new model of the atonement - Gorman, Michael J., 1955- (Eugene, Oregon : Cascade Books, an imprint of Wipf and Stock Publishers, 2014)
"In this groundbreaking book, Michael Gorman asks why there is no theory or model of the atonement called the "new covenant" model, since this understanding of the atonement is likely the earliest in the Christian tradition, going back to Jesus himself. Gorman argues that most models of the atonement over-emphasize the penultimate purposes of Jesus' death and the "mechanics" of the atonement, rather than its ultimate purpose: to create a transformed, Spirit-filled people of God. The New Testament's various atonement metaphors are part of a remarkably coherent picture of Jesus' death as that which brings about the new covenant (and thus the new community) promised by the prophets, which is also the covenant of peace. Gorman therefore proposes a new model of the atonement that is not really new at all--the new- covenant model. He argues that this is not merely an ancient model in need of rediscovery, but also a more comprehensive, integrated, participatory, communal, and missional model than any of the major models in the tradition. Life in this new covenant, Gorman argues, is a life of communal and individual participation in Jesus' faithful, loving, peacemaking death."--Book cover.
Introduction: Refocusing the atonement -- The promise of the new covenant -- Cross and new covenant in the New Testament : the gospels and Acts -- Cross and new covenant in the New Testament : from Paul to Revelation -- Baptized into the Messiah's death : new-covenant practices of cruciform faithfulness -- Baptized into the Messiah's death : new-covenant practices of cruciform love -- The (new) covenant of peace -- Baptized into the Messiah's death : new-covenant practices of Cruciform peace -- Conclusion: The integrative new-covenant model of the atonement : participation and performance.
Includes bibliographical references (pages 239-249) and indexes.
Print version record.
Keywords: Atonement; RELIGION / Christian Theology / Christology; Electronic books